Comparison between the political information consumption of the general voter and specialized audiences. The cases of the Argentinian, Spanish and Venezuelan 2015 elections - Beatriz Fernández, Carmen (2017)
Different publics consume political information in different ways. The pattern of consumption of political information varies according to the different publics, not only in their intensity of use, but also in the various communication outlets used to inform themselves. This article compares the patterns of political information for the most interested publics (journalists, academics, consultants and political leaders) with general voters, taking as a case the study of the Argentinian, Spaniard and Venezuelan elections of 2015.